Development and characterization of gelatin‐based hydrogels, emulsion hydrogels, and bigels: A comparative study. Issue 8 (7th October 2014) - Satapathy, Sitipragyan; Singh, Vinay K.; Sagiri, Sai Sateesh; Agarwal, Tarun; Banerjee, Indranil; Bhattacharya, Mrinal K.; Kumar, Naresh; Pal, Kunal
ABSTRACT This study was designed to examine the physicochemical and electrical properties of gelatin‐based hydrogels, emulgels, and bigels. The chemical studies suggested an increase in hydrogen bonding in the emulgel and bigel when sesame oil (SO; representative vegetable oil) and SO organogel (OG; representative OG) were incorporated within the gelatin matrix. The emulgel and bigel showed better mechanical properties and higher electrical impedances compared to the hydrogel. The hydrogel showed similar swelling at pH 1.2 and 7.2. The swelling of the emulgel and bigel was higher at pH 7.2. The formulations were found to be highly hemocompatible; this indicated their biocompatible nature. Ciprofloxacin, a model antimicrobial drug, was incorporated within the formulations. The release of the drug was found to be diffusion‐mediated. The antimicrobial efficiency of all of the drug‐loaded formulations was found to be equivalent. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41502.